(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
The article aims to study the conflicting relationship between the occupation of urban land and the preservation of the environment. The disorderly growth of Brazilian urban centers, intensified by the growing rural exodus in the 20th century, entailed severe damage and threats to the environmental balance, whose effects are capable of affecting present and future generations. The need to fulfill the social function of property is intrinsically related to the observance of environmental protection in urban developments and occupations. In addition to guaranteeing decent housing for citizens, the government also has a duty to demand environmental preservation in urban centers and in the surroundings of cities. The land regularization of already consolidated occupations must be concerned not only with legal issues, but, by legal imperative, must also encompass environmental, social and urban measures. Thus, alongside the necessary regularization and the inevitable and important development and growth of cities, there is an imperative concern with environmental preservation, whether on the part of public managers or on the part of the entire civil society.